Memahami Perilaku Perjalanan ke Pasar Induk Tani Kota Batu: Peran Variabel Sosial Ekonomi dan Aksesibilitas - Ahmad Ricky Alighan; Ludfi Djakfar; Agus Dwi Wicaksono; Muh Miftahulkhair (Postgraduate, University of Mataram, 2025)
This study aims to analyze the factors influencing trip attraction to the Among Tani Main Market in Batu City and to develop a trip attraction model that can support transportation planning and market management. Primary data were collected through a questionnaire survey of 404 respondents, while secondary data were obtained from relevant agencies. Descriptive statistics were used to describe visitors’ socio-economic and travel behavior, and multiple linear regression analysis was applied to identify the dominant variables affecting visit frequency. The results show that most visitors are female, aged 31–40, with senior high school education, self-employed, and earning IDR 1–2.5 million per month. The majority use motorcycles, travel an average distance of 5–10 km, and spend 15–30 minutes to reach the market. Of the 20 independent variables tested, five were significant: travel distance, travel time, shop area, parking area, and building size. Distance and time negatively affect visit frequency, while the three infrastructure-related variables have positive effects, with shop area being the most dominant factor. The study concludes that accessibility and infrastructure capacity are more influential than socio-economic factors. These findings provide practical implications for market management and transportation planning in Batu City to enhance visit attraction and support sustainable urban development.